2020
DOI: 10.3390/ijms21082966
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Function of Bicellular Tight Junctions in Skin and Oral Wound Healing

Abstract: Bicellular tight junctions are multiprotein complexes that are required for maintenance of barrier function and fence function in epithelial tissues. Wound healing in the oral cavity leads to minimal scar formation compared to the skin, and the precise mechanisms for this regenerative response remain to be elucidated. We hypothesized that oral and skin tissues express a different tight junction repertoire both at baseline and during the wound healing response, and that these molecules may be critical to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…F ample, the rate of wound healing and the incidence of scarring are different betwee and epidermal keratinocytes as the healing rate and properties are more effective oral epithelium [112]. Furthermore, keratinocytes from the two sources differ in ce interactions in terms of their expression of tight junctions, which increase epid keratinocyte permeability upon histamine stimulation [113]. Similarly, the secretory tions of epidermal and bronchial keratinocytes can be different according to the tr For example, bronchial keratinocytes can release cytokines in response to bisphe Such an effect has not been illustrated in epidermal keratinocytes [114].…”
Section: Stratification Of the Retrieved Articlesmentioning
confidence: 99%
“…F ample, the rate of wound healing and the incidence of scarring are different betwee and epidermal keratinocytes as the healing rate and properties are more effective oral epithelium [112]. Furthermore, keratinocytes from the two sources differ in ce interactions in terms of their expression of tight junctions, which increase epid keratinocyte permeability upon histamine stimulation [113]. Similarly, the secretory tions of epidermal and bronchial keratinocytes can be different according to the tr For example, bronchial keratinocytes can release cytokines in response to bisphe Such an effect has not been illustrated in epidermal keratinocytes [114].…”
Section: Stratification Of the Retrieved Articlesmentioning
confidence: 99%
“…However, it has been hypothesized that the differential expression of the tight junctions repertoire in the oral cavity may be involved in the scarring process in this tissue. In a murine model, the expression of claudin 1 and occludin was analyzed and it was concluded that there are genes differentially expressed in oral tissues that can contribute to the mechanisms that lead to the expression of scar phenotypes in response to injuries ( 40 ). Keratin also connects to actin through adherent junctions and desmosomes forming a mechanical unit, while adherent junctions act as mechanosensors in the transduction of mechanical forces between the plasma membrane and the cytoskeleton of actomyosin.…”
Section: Anatomy Of Epithelia-malt In Oral and Gi Tractsmentioning
confidence: 99%
“…1 ). Changes to tight-junction proteins, including ZO-2 and OCLDN, are important in wound-healing responses and RPE barrier integrity and function [ 74 ], and therefore the IL-33-mediated response of mast cell function could influence the outcome in this context. Furthermore, the importance of IL-33 in resolving inflammation is highlighted in a study by Augustine et al that shows following retinal detachment, IL-33 deficient mice display chronic inflammatory responses and increased severity of retinal degeneration [ 68 ].…”
Section: Interleukin-33 Modulation Of Diseasementioning
confidence: 99%